2022
DOI: 10.1002/dac.5348
|View full text |Cite
|
Sign up to set email alerts
|

On the realization of VANET using named data networking: On improvement of VANET using NDN‐based routing, caching, and security

Abstract: Summary Named data networking (NDN) presents a huge opportunity to tackle some of the unsolved issues of IP‐based vehicular ad hoc networks (VANET). The core characteristics of NDN such as the name‐based routing, in‐network caching, and built‐in data security provide better management of VANET proprieties (e.g., the high mobility, link intermittency, and dynamic topology). This study aims at providing a clear view of the state‐of‐the‐art on the developments in place, in order to leverage the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 175 publications
(327 reference statements)
0
6
0
Order By: Relevance
“…In the year 2022 there was a variety of review research from different perspectives, especially regarding vehicular NDN [43,44], security and privacy over NDN [45,46], mobility on NDN [47], as well as forwarding and routing on NDN [48]. There were significant discussions on routing, caching, and security mechanisms.…”
Section: Current Review Trendmentioning
confidence: 99%
“…In the year 2022 there was a variety of review research from different perspectives, especially regarding vehicular NDN [43,44], security and privacy over NDN [45,46], mobility on NDN [47], as well as forwarding and routing on NDN [48]. There were significant discussions on routing, caching, and security mechanisms.…”
Section: Current Review Trendmentioning
confidence: 99%
“…The authors in [22] proposed a hierarchical, cellular, and cluster-based architecture for NDN-based VANET, where nodes dubbed "barycenters" take the responsibility for communicating with a cellular layer in each cluster. For the interested reader, several other studies can be found in surveys such as [23][24][25][26][27][28], which include research challenges on implementing NDN-based VANET.…”
Section: Realization Of Ndn-based Vanetmentioning
confidence: 99%
“…There are several solutions for content dissemination in NDN-based VANET. This work does not pretend to perform an exhaustive survey on the state of the art of forwarding schemes; existing surveys on this matter include [6,17,28,32] and the ones mentioned in Section 1.3.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations